Morphology, morphometry, and phylogeny of the protozoan parasite, Eimeria labbeana-like (Apicomplexa, Eimeriidae), infecting Columba livia domestica - Albasyouni, Shurug; Abdel-Gaber, Rewaida; Al Quraishy, Saleh; Al-Shaebi, Esam M.; Mohammed, Osama B. (Frontiers in Veterinary Science, 2024)
Eimeria spp. are intracellular protozoan parasites of the phylum Apicomplexa causing economic losses to various wild and domestic animals. An eimerian species infecting Columba livia domestica was identified in this study using morphological and molecular (DNA amplification of the 18S rRNA and ITS-1 genes) diagnostic techniques. A total of 15 faecal samples were examined by floatation technique, a prevalence rate of 60%was was reported. Eimerian oocysts were sporulated in 2.5% potassium dichromate solution. Sporulated oocysts were identified as Eimeria labbeana-like, after morphometry with typical bi-layered wall with spherical to subspherical oocysts morphology. A polar granule is present, but no micropyle or oocyst residuum. Sporocysts are elongated ovoidal with stieda body. Sporocyst residuum with many granules and sporozoites with refractile bodies and nucleus. Both 18S and ITS1 rRNA sequences have been deposited in GenBank database. DNA sequences from the partial 18S rDNA generated from the oocysts were found to be related to eimerian and isosporan parasites found in domestic pigeons. For the first time, ITS1 DNA sequences for E. labbeana-like were provided. The necessity of using molecular techniques to describe pigeon intestinal coccidian parasites in conjunction with traditional morphology-based tools was emphasized in this work in order to understand the biology of such parasites.